Témoins archéologiques de l’estive médiévale et moderne : évolution typo-chronologique et spécificités de l’habitat agropastoral sur le haut Forez entre le xie s. et le xviiie s. (Massif central oriental, France) - Antoine Scholtès; Priscille Chapuis; Jacques Verrier; Christian Le Barrier; Christophe Mathevot; Hervé Cubizolle (Revue Archéologique du Centre de la France)
Since 2016, research carried out on the “Hautes-Chaumes des Monts du Forez” has identified a significant number of archaeological remains linked with the pastoral management of this territory between the second part of the Middle Ages and the end of the modern Times (12th-18th centuries). The typo-chronological evolution of the settlements and their architectural features reflects a progressive structuring of pastoralism closely linked to the needs and orientations of the regional economy (Forez, Dore, Limagne). Although it has grown and intensified over the centuries, livestock farming has retained a local character, adopted by the landowners and peasant communities in charge of the pastures. The will is dictated by the desire to preserve resources in order to perpetuate the activity over time. The access to summer pastures is therefore strictly reserved to local livestock. This status is important because it distinguishes the Forezian pastoralism from that of Cézallier, Cantal, Aubrac and Velay, where the transhumance predominates. In the Hautes-Chaumes, pastoralists are responsible for the maintenance of the land and position themselves as the main actors in the artificialization of the landscape. Pastoral housing reflects this age-old dynamic through its distribution and architectural forms.